Wednesday

April 16, 2014

April 16, 2014

Posted by **isha** on Thursday, February 12, 2009 at 9:09pm.

- math -
**Reiny**, Thursday, February 12, 2009 at 10:53pmthe sum of the roots of the original is 3/2

the product of the roots is -2

so a+b = 3/2

ab = -2

sum of new roots = 1/a + 1/b = (a+b)/(ab)

= (3/2) / -2 = -3/4

product of new roots - (1/a)(1/b) = 1/(ab) = -1/2

so the new equation is

x^2 + (3/4)x - 1/2 = 0 or

4x^2 + 3x - 2 = 0

based on the theorem that for

ax^2 + bx + c = 0

the sum of the roots is -b/a and

the product of the roots is c/a

**Related Questions**

Algebra - Given the roots, 1/2 and 4, find: (A) The quadratic equation 2x^2-9x+4...

Algebra2 - Find the polynomials roots to each of the following problems: #1) x^2...

maths - Given that a and b are the roots of the quadratic equation 2x^2 - 4x +3...

Cubic Equations - I have three that I need help with if possible. 1. Solve 2x^3...

Precalculus - "Show that x^6 - 7x^3 - 8 = 0 has a quadratic form. Then find the ...

algebra - 1)Solve by factoring:5x^2=4-19x answer=-4,1/5 2)Which quadratic ...

Math (Algebra) - If the ratio of the roots of the quadratic equation x^2−...

Algebra - Find the number of integer quadruples (a,b,c,d) with 0\leq a,b,c,d \...

Algebra - Find the number of integer quadruples (a,b,c,d) with 0\leq a,b,c,d \...

math - Still looking at how to solve these... Both are cubic polynomials? 43x^3...